Checkpoint inhibitors in patients with metastatic renal cell carcinoma: Results from the International Metastatic Renal Cell Carcinoma Database Consortium. Issue 18 (11th October 2018) - Yip, Steven M.; Wells, Connor; Moreira, Raphael; Wong, Alex; Srinivas, Sandy; Beuselinck, Benoit; Porta, Camillo; Sim, Hao‐Wen; Ernst, D. Scott; Rini, Brian I.; Yuasa, Takeshi; Basappa, Naveen S.; et al.
Abstract : BACKGROUND: To the authors' knowledge, outcomes and prognostic tools have yet to be clearly defined in patients with metastatic renal cell carcinoma (mRCC) who are treated with immuno‐oncology (IO) checkpoint inhibitors (programmed death‐ligand 1 [PD‐L1] inhibitors). In the current study, the authors aimed to establish IO efficacy benchmarks in patients with mRCC and update patient outcomes in each International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) prognostic class. METHODS: A retrospective analysis was performed using the IMDC database with data from 38 centers. It included patients with mRCC who were treated with ≥1 line of IO. Overall response rates (ORRs), duration of treatment (DOT), and overall survival (OS) were calculated. Patients were stratified using IMDC prognostic factors. RESULTS: A total of 687 patients (90% with clear cell and 10% with non‐clear cell) were included. The ORR was 27% in evaluable patients (461 patients). In patients treated with first‐line nivolumab and ipilimumab (49 patients), the combination of PD‐L1 inhibitor and vascular endothelial growth factor inhibitor (72 patients), and PD‐L1 inhibitor (51 patients), the ORR was 31%, 39%, and 40%, respectively, and the median DOT was 8.3 months, 14.7 months, and 8.3 months, respectively. The ORR for second‐line, third‐line, and fourth‐line nivolumab was 22%, 24%, and 26%, respectively. The median DOT was 5.7 months, 6.2 months, and 8.3 months, respectively, in the second‐line, third‐line, and fourth‐line settings. When segregated into IMDC favorable‐risk, intermediate‐risk, and poor‐risk groups, the median OS rates for the first‐line, second‐line, third‐line, and fourth‐line treatment settings were not reached (NR), NR, and NR, respectively ( P  = .163); NR, 26.7 months, and 7.4 months, respectively ( P  < 0. 0001); 36.1 months, 28.2 months, and 11.1 months, respectively ( P  = .016); and NR, NR, and 6.7 months, respectively ( P  = .047). CONCLUSIONS: The ORR was not found to deteriorate from the first‐line to the fourth‐line of IO therapy. In the second line through fourth line, the IMDC criteria appropriately stratified patients into favorable‐risk, intermediate‐risk, and poor‐risk groups for OS. Abstract : The overall response rate to checkpoint inhibitors does not deteriorate when checkpoint inhibitors are used from the first‐line to fourth‐line of therapy for patients with metastatic renal cell carcinoma. In the second‐line, third‐line, and fourth‐line treatment settings, the International Metastatic Renal Cell Carcinoma Database Consortium criteria appear to appropriately stratify patients into favorable‐risk, intermediate‐risk, and poor‐risk groups for overall survival.